2020
DOI: 10.1055/a-1113-7777
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Management, and Treatment Outcomes of Primary Hypophysitis: A Monocentric Cohort

Abstract: Primary hypophysitis (PH) is a rare autoimmune inflammatory disease of the pituitary gland. The aim of the study was to evaluate clinical characteristics, disease management, and outcomes of cases with PH. Medical records of PH patients admitted to Hacettepe University Hospital between 1999 and 2017 were analyzed retrospectively. Paraffin-embedded pathology blocks were obtained for both re-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Thirteen studies [5][6][7][8][9][10][15][16][17][18][19][20][21] , involving a total of 241 patients, reported that LYH onset in female patients is related to pregnancy. Fifteen studies [5,[7][8][9][10][11][12][14][15][16][17][18][19][20][21] , involving a total of 340 patients, reported an association between LYH and other autoimmune diseases. In both study series, heterogeneity analysis revealed that there was statistical heterogeneity; thus, the random effects model was used for combined analysis.…”
Section: Patient Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies [5][6][7][8][9][10][15][16][17][18][19][20][21] , involving a total of 241 patients, reported that LYH onset in female patients is related to pregnancy. Fifteen studies [5,[7][8][9][10][11][12][14][15][16][17][18][19][20][21] , involving a total of 340 patients, reported an association between LYH and other autoimmune diseases. In both study series, heterogeneity analysis revealed that there was statistical heterogeneity; thus, the random effects model was used for combined analysis.…”
Section: Patient Featuresmentioning
confidence: 99%
“…All 17 studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , involving a total of 364 patients, reported headache as a symptom caused by LYH. Fifteen studies [6][7][8][9][10][11][12][13][15][16][17][18][19][20][21] , involving a total of 350 patients, reported visual field loss and visual impairment caused by LYH.…”
Section: Sella Mass-effect Symptomsmentioning
confidence: 99%
See 3 more Smart Citations